On asymptotically lacunary statistical equivalent of order a of difference sequences - Et, Mikail; Sengul, Hacer; Cinar, Muhammed (Amer Inst Physics, 2015)
In this study, we introduce and examine the concepts of 4-asymptotically statistical equivalent of order a and strong Delta(m)(theta) asymptotically equivalent of order a of sequences. Also, we give some relations connected to these concepts.
International Conference on Advancements in Mathematical Sciences (AMS) -- NOV 05-07, 2015 -- Antalya, TURKEY
Keywords: Asymptotically statistical equivalent; Difference sequence; Lacunary sequence